2020
DOI: 10.19045/bspab.2020.90109
|View full text |Cite
|
Sign up to set email alerts
|

Sea buckthorn Hippophae rhamnoides a non-conventional source of edible oil

Abstract: Obtaining edible oil from animals and plant sources is an ancient practice of the people in the tropical regions of the globe. Industrialization of oil and fats began with the creation of a cotton seed mill, due to higher demand several different plants have been studied to get good and healthy oil and fats. In this research the fixed oil from the berries of Sea Buckthorn was characterized and studied for its fatty acid composition by biochemical tests and Gas Chromatography Mass Spectroscopy (GCMS). The chemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…Van Nieuwenhove et al ( 2019 ) reported high content of punicic (omega‐5) and jacaric acids in pomegranate ( Punica granatum ) and jacaranda ( Jacaranda mimosifolia ) seed oils, CLnA, with potent anticarcinogenic components. Rashid ( 2020 ) reported 28%–30%, 36%–40%, and 17%–20% omega‐3, 6, and 9 FAs in sea buckthorn berries oil ( Hippophae rhamnoides ), respectively. Prasad et al ( 2021 ) reported that oil from Echium plantagineum , Buglossoides, hemp, and black currant seeds were natural sources of stearidonic acid (SDA).…”
Section: Resultsmentioning
confidence: 99%
“…Van Nieuwenhove et al ( 2019 ) reported high content of punicic (omega‐5) and jacaric acids in pomegranate ( Punica granatum ) and jacaranda ( Jacaranda mimosifolia ) seed oils, CLnA, with potent anticarcinogenic components. Rashid ( 2020 ) reported 28%–30%, 36%–40%, and 17%–20% omega‐3, 6, and 9 FAs in sea buckthorn berries oil ( Hippophae rhamnoides ), respectively. Prasad et al ( 2021 ) reported that oil from Echium plantagineum , Buglossoides, hemp, and black currant seeds were natural sources of stearidonic acid (SDA).…”
Section: Resultsmentioning
confidence: 99%